Zooming in: an ethnographic study of visual journalism for smartphones - journalistic roles and routines at South Africa's largest graphics unit, Graphics24 - Gouws, Andries Jacobus (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2018)
This study examines the changing roles of graphics journalists in the digital era at Graphics24, the largest information graphics newsroom in South Africa, in the context of their work for Netwerk24, an online news site published in Afrikaans with a strong focus on mobile-first news. The study examines the discursive construction of these new journalistic roles in the digital era where even the core conceptualisation of what journalism is, is being re-examined. It considers external factors affecting the discourse of change, drawing on a hierarchy of influences analytical model, as well as norms specific to the creation of information graphics. Data for this study was gathered by using ethnographic immersion and semi-structured interviews. This study specifically looks at graphics journalists working in a mobile-first environment, and how the pressures of producing information graphics for consumption on smartphones affects their roles. Evidence of two widely differing discourses in the Graphics24 and Netwerk24 newsrooms was found. Visual journalists in this study have created a discourse around being distinct "service providers" , rather than mobile-first journalists, who do not see the need for full integration in the fast-paced mobile news environment of Netwerk24. Word-centric journalists have, by contrast, created a mobile-first discourse. They experience the separateness of the graphics team as a barrier that impedes the creation of good information graphics for mobile phone consumption. Although this is a very localised study in a very particular context, this study contributes to broader thinking in what is a very under-researched field: The changing roles of visual journalists in the digital era and the discursive construction of these roles. The study suggests that even in the digital era where the definition of newsrooms has become much more fluid and less fixed physically, ethnographic methods can still offer a meaningful way to explore journalistic roles.
Keywords: Journalism -- Technological innovations -- South Africa; Smartphones; Visual communication -- Digital techniques; News Web sites -- South Africa; Online journalism -- South Africa; Information visualization; Graphic arts; Graphics24; Netwerk24